Rationally derived drug combinations with the novel Mcl-1 inhibitor EU-5346 in breast cancer - Vallet, Sonia; Schneeweiss, Andreas; Jäger, Dirk; Podar, Klaus (Breast cancer research and treatment, 2019)
Purpose: Recent studies have emphasized a key role for the anti-apoptotic Bcl-2 family member Mcl-1 in conferring tumor cell survival and drug resistance in breast cancer (BC). Mcl-1 inhibitors, such as the BH3-mimetic EU-5346, therefore represent an exciting new class of targeting agents and are a current focus of widespread cancer-drug development efforts.Methods: ONCOMINE analysis was utilized to compare expression profiles of Bcl-2 family members across all major BC subgroups. Potential toxicities of EU-5346 were evaluated using iPS-generated cardiomyocytes, blood cells and astrocytes. The anti-BC cell activity of EU-5346-based therapies was evaluated using [3H]-thymidine uptake and spheroid-forming assays as well as immunoblotting and the Chou-Talalay method. Protein level-based activity of EU-5346, the specific anti-Bcl-2 inhibitor ABT-199 and the specific anti-Bcl-xL inhibitor WEHI-539 was verified in Mcl-1Δ/null versus Mcl-1wt/wt MEFs. Results: We previously demonstrated significant anti-tumor activity of EU-5346 in all BC subtypes. Our present results go further and suggest that EU-5346 may induce limited adverse events such as cardiotoxicity, hematotoxicity, and neurotoxicity, frequently observed with other BH3 mimetics. As demonstrated by our mathematical scoring model, the prediction of EU-5643-induced IC50 not only relies on the protein level of Mcl-1 but also on Bak, Bim, and Noxa. Synergistic anti-BC activity of low-dose EU-5346 with the BH3 mimetics ABT-199 or WEHI-539 was observed only in those BC cells expressing Bcl-2 or Bcl-xL, respectively. Similarly, when combined with tamoxifen or trastuzumab, low-dose EU-5346 induced significant anti-BC activity in hormone receptor positive or Her2-positive BC cells, respectively. Finally, EU-5346 in combination with paclitaxel induced synergistic anti-BC activity in both paclitaxel-sensitive and paclitaxel-resistant TNBC cells. Conclusion: These data strongly support the further clinical development of EU-5346 to improve BC patient survival.
First Online: 29 October 2018
Gesehen am 11.07.2019